The Using Of Audio Visual (Multimedia Projector) To Improve Student Learning Outcomes In The Subject Of Islamic Culture History VIIth C-Class at MTs al-Ikhlas Setupatok - Irpandi; Abidin, Andi Rahmat (IAIN Ambon, 2024)
This research aims to improve learning outcomes in the subject History of Islamic Culture for Class VII C students at MTs Al Ikhlas Setupatok. The research that the researcher conducted used a qualitative approach with the type of research, namely Classroom Action Research (PTK). The sequence of research activities includes (1) Planning, (2) Implementation, (3) Observation, (4) Reflection. Data collection uses interview, observation and documentation techniques. Meanwhile, for the analysis, the author uses the Qualitative Descriptive Analysis technique. The source of the research is Class VII C MTs Al Ikhlas Setupatok Students, Mundu District, Cirebon Regency. The results of the research show that the Audio Visual Multimedia Projector Media in the Islamic Cultural History Subject with material on the event of the Prophet Muhammad SAW's Hijrah to Medina was taken from the theme of the Wisdom of the Prophet Muhammad SAW, Creating Peace, and was able to improve student learning outcomes in the Class VII C Islamic Cultural History Subject at MTs Al Ikhlas Setupatok. These results have met the indicators of success and reached the standard criteria for success or received a score of >70. Apart from that, classical student learning outcomes from cycle one and cycle two are said to have increased, namely in cycle I 13 or 34.210% experienced completeness and in cycle two it increased to 38 or 100% experienced completeness.